Prevalence and genotypic distribution of non-epidermolytic ichthyosis in Italian Golden Retrievers - Maria Grazia De Iorio; Michele Polli; Sara Ghilardi; Stefano Frattini; Mara Bagardi; Alessandra Paganelli; Maria Cristina Cozzi; Kenza Seghrouchni; Paola Giuseppina Brambilla; Giulietta Minozzi (PLoS ONE, 2026)
Non-epidermolytic ichthyosis (NEI) is a hereditary skin disorder affecting several dog breeds, most notably the Golden Retriever. It is primarily caused by a loss-of-function variant in the PNPLA1 gene, while a second, less common form is associated with a deletion in the ABHD5 gene. This retrospective study aimed to assess the prevalence and temporal trends of both mutations in Golden Retrievers tested in Italy between 2017 and September 2025. A total of 508 genetic tests were analyzed, including 463 dogs tested for the PNPLA1 mutation, 42 for the ABHD5 deletion, and 3 for both variants. DNA was extracted from blood or buccal samples and analyzed by real-time PCR followed by confirmatory Sanger sequencing. Among the PNPLA1 tested dogs, 42% were clears (wt/wt), 37% carriers (wt/mut), and 21% affected (mut/mut), with calculated allele frequencies of 60% wild-type and 40% mutant. A significant temporal decline in mutant allele frequency was observed, accompanied by an increasing number of animals tested over time, suggesting growing interest in genetic screening and its impact on selective breeding. Conversely, all dogs tested for the ABHD5 deletion were wild-type, supporting its rarity in the breed. Overall, these findings confirm that PNPLA1 -related ichthyosis remains one of the most prevalent hereditary disorders in Golden Retrievers, although its frequency is decreasing. The results emphasize the effectiveness of genetic testing in disease prevention and highlight the importance of continued monitoring to maintain genetic health within the breed.